Limiting Factors Affecting the Ionic Conductivities of LATP/Polymer Hybrid Electrolytes - Adrien Méry; Steeve Rousselot; David Lepage; David Aymé-Perrot; Mickael Dollé (Batteries, 2023)
All-Solid-State Lithium Batteries (ASSLB) are promising candidates for next generation lithium battery systems due to their increased safety, stability, and energy density. Ceramic and solid composite electrolytes (SCE), which consist of dispersed ceramic particles within a polymeric host, are among the preferred technologies for use as electrolytes in ASSLB systems. Synergetic effects between ceramic and polymer electrolyte components are usually reported in SCE. Herein, we report a case study on the lithium conductivity of ceramic and SCE comprised of Li1.4Al0.4Ti1.6(PO4)3 (LATP), a NASICON-type ceramic. An evaluation of the impact of the processing and sintering of the ceramic on the conductive properties of the electrolyte is addressed. The study is then extended to Poly(Ethylene) Oxide (PEO)-LATP SCE. The presence of the ceramic particles conferred limited benefits to the SCE. These findings somewhat contradict commonly held assumptions on the role of ceramic additives in SCE.